Analyzing time-varying tail dependence between leveraged loan and debt markets in the U.S. economy - Tiwari, A.K.; Abakah, E.J.A.; Trabelsi, N.; Lee, C. (International Review of Finance, 2023)
This study analyzes the time-varying dependence between U.S. leveraged loan and debt markets within a highly linked financial system using a quantile-based, time-varying connectedness framework to determine the hedging benefits of leveraged loans for financial investors at various quarters. Based on daily closing price data from November From October 28, 2008, to October 3, 2023, the evidence demonstrates considerable (moderate) spillovers across the leveraged loan and debt markets for severe (normal) occurrences, with additional results indicating symmetric interaction. In terms of risk spillover, we also affirm the dominance of short-term fixed-income instruments over leveraged loans and long-term bonds. These findings indicate that no hedging or diversification occurred among the investigated markets.
Research Article
Keywords: dynamic connectedness; leveraged loans; treasury bonds